Comparative study on effects of two different types of titanium dioxide nanoparticles on human neuronal cells - Valdiglesias, V. (2014)
Titanium dioxide (TiO2) are among most frequently used nanoparticles (NPs). They are present in a variety of consumer products, including food industry in which they are employed as an additive. The potential toxic effects of these NPs on mammal cells have been extensively studied. However, studies regarding neurotoxicity and specific effects on neuronal systems are very scarce and, to our knowledge, no studies on human neuronal cells have been reported so far. Therefore, the main objective of this work was to investigate the effects of two types of TiO₂ NPs, with different crystalline structure, on human SHSY5Y neuronal cells. After NPs characterization, a battery of assays was performed to evaluate the viability, cytotoxicity, genotoxicity and oxidative damage in TiO₂ NP-exposed SHSY5Y cells. Results obtained showed that the behaviour of both types of NPs resulted quite comparable. They did not reduce the viability of neuronal cells but were effectively internalized by the cells and induced dose-dependent cell cycle alterations, apoptosis by intrinsic pathway, and genotoxicity not related with double strand break production. Furthermore, all these effects were not associated with oxidative damage production and, consequently, further investigations on the specific mechanisms underlying the effects observed in this study are required.